2016
DOI: 10.12691/ijcd-1-1-9
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of IgA/IgG DGP/tTG Screen Assay for Celiac Disease Detection among Symptomatic and at Risk Young Children

Abstract: Background: It has been postulated that IgA anti tissue-transglutaminase (tTG) and anti-endomisium (EMA) antibodies can be false negative in young children.ESPGHAN recommended for seronegative children younger than 2 years old with clinical suspicion of celiac disease to perform duodenal biopsies. Recent studies sugested that the combined assay for IgA/IgG deamidated gliadin peptides (DGP) and tTG can detect celiac disease among seronegative young children. Aim: To assess if the new combined assay with synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Our results provide confirmatory evidence of this finding, but also show that these serological changes provide strong evidence for the characteristic histopathological changes of untreated celiac disease. Recent evidence suggests that detection of all clinical forms of CD may be most effective with a combination of IgA tTG antibodies coupled with autoantibodies against deaminated gliadin (DGP) [17,18]. Specialized groups have also supported the value of serological screening in adult CD [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide confirmatory evidence of this finding, but also show that these serological changes provide strong evidence for the characteristic histopathological changes of untreated celiac disease. Recent evidence suggests that detection of all clinical forms of CD may be most effective with a combination of IgA tTG antibodies coupled with autoantibodies against deaminated gliadin (DGP) [17,18]. Specialized groups have also supported the value of serological screening in adult CD [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of celiac disease was made according to intestinal biopsy findings. They found the sensitivity of combined IgA/IgG DGP/tTG screen assay (95.4 %) higher than both antitTGA (86.3%) and anti-EmA (91%) antibodies in this age group of children [12]. They concluded that better performance of this combined tests might preclude repeated intestinal biopsies in young symptomatic children who have negative tTG/EmA serology.…”
mentioning
confidence: 97%
“…On the other hand, some studies demonstrated superior diagnostic value of anti-tTG to anti-DGP antibodies even in patients younger than 2 years-old [11]. In this first issue of the Journal, Oana et al [12] investigated the accuracy of these antibodies in symptomatic infants. They evaluated the diagnostic value of combined IgA/IgG DGP/tTG screen assay in anti-IgA tTG or anti-EmA negative children younger than 2 yearsold.…”
mentioning
confidence: 99%
“…Using different serologic tests permitted a better selection of cases for intestinal biopsy in celiac patients. In clinical practice, serological tests for CD are useful in identifying patients who require intestinal biopsy findings to diagnose this condition [2]. Serological screening for CD in a population with associated risk factors is now considered the most efficient strategy, taking into account cost-effectiveness.…”
mentioning
confidence: 99%
“…Serological screening for CD in a population with associated risk factors is now considered the most efficient strategy, taking into account cost-effectiveness. The efficiency of this serological screening is to identify the cases with atypical or oligo-symptomatic forms of CD [2].…”
mentioning
confidence: 99%